2021
DOI: 10.1186/s43094-021-00203-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical applications of citric acid

Abstract: Background Citric acid (CA) is a universal plant and animal-metabolism intermediate. It is a commodity chemical processed and widely used around the world as an excellent pharmaceutical excipient. Notably, CA is offering assorted significant properties viz. biodegradability, biocompatibility, hydrophilicity, safety, etc. Therefore, CA is broadly employed in many sectors including foodstuffs, beverages, pharmaceuticals, nutraceuticals, and cosmetics as a flavoring agent, sequestering agent, buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…The medicinal value of these compounds was already reported by many researchers i.e., in many food and pharmaceutical industries, citric acid is used as an emulsifier, flavorant, sequestrant, buffering, acidulant, and preservative (Verhoff, 2000;Nangare et al, 2021). Quininic acid is one of the organic acids, and it was also extracted from Eucalyptus globulus and employed as an astringent and a precursor for the synthesis of novel medications (Shi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal value of these compounds was already reported by many researchers i.e., in many food and pharmaceutical industries, citric acid is used as an emulsifier, flavorant, sequestrant, buffering, acidulant, and preservative (Verhoff, 2000;Nangare et al, 2021). Quininic acid is one of the organic acids, and it was also extracted from Eucalyptus globulus and employed as an astringent and a precursor for the synthesis of novel medications (Shi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The surface that was created is hemocompatible and allows for endothelization, while inhibiting smooth muscle cell adhesion and proliferation, overall improving the biocompatibility of the Mg alloy stents [ 105 , 106 ]. Extensive reviews of the role of citric acid as a crosslinker can be found in references [ 107 , 108 ].…”
Section: Citric Acid In Formulationsmentioning
confidence: 99%
“…Citric acid (H 4 Cit) is an essential component of the Krebs cycle and a universal intermediate in plant and animal metabolism. Its biocompatibility, hydrophilicity and general safety make citric acid a common component in foodstuffs, beverages, pharmaceuticals, cosmetics, etc (Nangare et al, 2021). Recently, Varbanets and co-workers have reported that germanium coordination compounds with citric acid combined with a second metal and ligand, such as Co and 1,10phenanthroline (phen), show high antihypoxic, cerebroprotective properties and have an activation effect on enzymes (Lukianchuk et al, 2019;Gudzenko et al, 2019a,b).…”
Section: Chemical Contextmentioning
confidence: 99%